Globalization and Disability Addiction in Working Populations: Unlocking the Global Correlates to Disability Addiction Calls for the Healthicization of Society. - Walker, Gabriela; Yockey, Mark; Wone, Bernard W. M. (International Journal of Mental Health & Addiction, 2023)
Addiction behavior and the resulting short-term or long-term disabilities continue to increase globally, especially during the current COVID pandemic. We analyze how national measures of 38 global indices correlate with national addiction-related disability rates resulting from four primary addictive substances: alcohol, tobacco, drugs, and food. We utilized a canonical correspondence analysis to explore the relationships between 38 political, economic, and cultural characteristics and years of life lived with a short-term or long-term health loss in 78 countries. The model selection approach reduced 38 global indices to 13 explanatory variables (final model: F = 5·64, p < 0.001 after 1000 permutations). Results show that the following factors are correlated with increased addiction disabilities stemming from obesity, alcohol, drug, and tobacco use: political stability; voice and accountability; control of corruption; economic freedom; women economic opportunity; Human Development Index; individuality; masculinity; long-term orientation; indulgence; uncertainty avoidance; personal contact; and religious diversity. Health care policy makers should consider that national culture, political attributes, and economic characteristics can influence national disability rates resulting from addictions.